COVID-19 outcomes in postmenopausal and perimenopausal females: Is estrogen hormone attributing to gender differences? - Ruchika Garg; Prabhat Agrawal; Ashish Gautam; Nikhil Pursnani; Mohita Agarwal; Arti Agarwal; Avantika Parihar; Anjana Pandey (Wolters Kluwer Medknow Publications, 2020)
Background: Globally, case fatality rate is more in males compared to females. Some studies have suggested. It is hypothesized that estrogen hormone may decrease susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS CoV-2.) Objective: The objective of the study was to evaluate the gender differences in SARS CoV-2 outcomes and to analyze if there are any differences in outcomes in premenopausal females compared to postmenopausal females. Materials and Methods: Patients tested positive for SARS CoV-2 through real-time reverse transcription-polymerase chain reaction by Thermo Fischer Taqpath assay approved by the Indian Council of Medical Research were included in the study. The data obtained was analyzed for the epidemiological, clinical, and laboratory characteristics from their medical records. Results: The mortality rate in females was 12.6%, whereas mortality in males was 19.4%. In between-group analysis, 8.6% (16/185) of females died in premenopausal age group versus 12.8% (27/211) in postmenopausal group. The proportion of females who expired due to COVID significantly differ by age and postmenopausal status X2 (1, n = 293) = 7.2, the P value is 0.007. The difference is statistically significant at P < 0.05. Postmenopausal women were more likely to expire due to COVID-19 infection compared to premenopausal women. Conclusion: The mortality rate in postmenopausal age group was greater than mortality in premenopausal females emphasizing the protection provided by estrogens hormone in them. Postmenopausal women are also at higher risk of severe COVID-19 infection than premenopausal women. Mortality is greater in males compared to females, further strengthening the role of estrogens.